Optimum structure design for finite precision implementation of digital systems - Hao, Jinxin (2008)
The finite word length (FWL) effects have been considered as one of the most important issues in digital system implementation. In this thesis, we design a series of optimal structures for digital filters and controllers, which can minimize the FWL effects in terms of stability robustness and roundoff noise gain.